Contributos para a caracterização do período tardiglaciar no Médio Vouga: a indústria lítica do Rôdo, Vau e Bispeira 8 - Gameiro, Cristina (2020)
The recent identification of three late Upper Palaeolithic sites in the Vouga valley is a valuable contribution to the definition of the Upper Palaeolithic chronostratigraphy in Portugal. This article presents a synthetic analysis of raw material procurement modalities, blank production, transformation and use of the lithic tools recovered at the Rôdo, Vau and Bispeira 8 sites. The results will be compared with data from analogous sites of Estremadura and the Côa Valley, in order to fine-tune the chrono-cultural attribution of the different human occupations identified at the three sites.